Assessing the Condition of Rock Tools through Waveform Analysis Techniques of Rock Drilling Induced Vibration Signals - Hettiarachchi, Don Sameera Wishwajith (Curtin University, 2016)
Detection of precise moment of button failure of a drill bit during a hard rock drilling process is vital to increase the efficiency in drilling. Sound generated during a hard rock drilling process was analysed using waveform analysis techniques. Wavelet transform analysis can detect the exact moment of button failure and the frequency range, which the failure occurred. Wavelet Transform is more effective than Fourier Transform and time series analysis in singularity detection.